1999
DOI: 10.1046/j.1525-1594.1999.06164.x
|View full text |Cite
|
Sign up to set email alerts
|

The Merit of Sintered PDLLA/TCP Composites in Management of Bone Fracture Internal Fixation

Abstract: Polyesters based on lactic acid have been reported in terms of safety and biodegradation in human beings for 2 decades. The greatest advantage of such material is its degradation conducted only by hydrolysis, whereby the ester backbones are supposed to be unchained in the aqueous condition. The final degradable products are carbon dioxide and water which can be metabolized and digested in the physiological environment. The goal of this study was aimed at developing a composite sintered with poly-DL-lactide (PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Composite materials thus seem more favorable for bone consolidation than do pure polymer materials, and have been shown in vitro to improve biological behavior. These results confirm hypotheses on PLA/ TCP 23,24,35,36, materials and, more generally, the absorbable polyester/calcium phosphate composites presented in the literature, 20 -22,25-28,37,38 where the presence of minerals in the polymer matrix promoted the proliferation and phenotype expression of osteogenous cells in vitro. These findings were also corroborated by the histological examinations, which indicated clearly that pure PLA implants were systematically surrounded by a layer of conjunctival tissue containing large numbers of macrophages, irrespective of the length of implantation, whereas bone tissue grew in direct contact with composite implants during the first few months and matured gradually until the end of the study period, with no marked macrophage activation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Composite materials thus seem more favorable for bone consolidation than do pure polymer materials, and have been shown in vitro to improve biological behavior. These results confirm hypotheses on PLA/ TCP 23,24,35,36, materials and, more generally, the absorbable polyester/calcium phosphate composites presented in the literature, 20 -22,25-28,37,38 where the presence of minerals in the polymer matrix promoted the proliferation and phenotype expression of osteogenous cells in vitro. These findings were also corroborated by the histological examinations, which indicated clearly that pure PLA implants were systematically surrounded by a layer of conjunctival tissue containing large numbers of macrophages, irrespective of the length of implantation, whereas bone tissue grew in direct contact with composite implants during the first few months and matured gradually until the end of the study period, with no marked macrophage activation.…”
Section: Discussionsupporting
confidence: 89%
“…We know that the acidification that accompanies the degradation of lactic acid polymers may also set off an inflammatory reaction. 1 In a systematic in vitro study, Lin et al 24 measured the pH of solutions containing a variety of PDLLA/TCP composite materials. The pH stabilized at 2.3 for a pure polymer material and 5 for all the materials containing mineral, which shows the effect of ␤-TCP on the acidity of the solution.…”
Section: Discussionmentioning
confidence: 99%
“…Mononuclear cells were found in a band along von Kossa stained calcium phosphate (CaP) analogous to osteoblasts lining up along mineralizing fronts of remodeled bone tissue. This behavior was not seen with the PLGA scaffolds and is similar to results seen with other polymer/CaP constructs [25], [26] suggesting that the HA component in PLGA/HA scaffolds can induce new mineralized bone growth without the inclusion of exogenous growth factors or cells.…”
Section: Resultssupporting
confidence: 78%
“…Stabilization of pH around an implant is of particular interest [14] and has been demonstrated by the addition of alkaline compounds, for example calcium phosphates [16,21] or bioactive glasses [22,23]. Lin et al [24] have shown that microsized and crystalline tricalcium phosphate (TCP) with low surface area used as filler in poly(α-hydroxy acids) resulted in decelerated degradation of the polymer and induced adverse mechanical properties during degradation [16]. A possibility to overcome this limitation can be the reduction of the filler particle size [25] to achieve enhanced dispersion and improved mode of action of tricalcium phosphate filler.…”
Section: Introductionmentioning
confidence: 99%